2021
DOI: 10.1039/d1ma00094b
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-compatible, gold nanoisland anchored 1D aligned ZnO heterojunction nanofibers: unveiling the NO2 sensing mechanism with operando photoluminescence studies

Abstract: Production and alignment of heterojunction metal oxide semiconductor nanomaterials-based sensing elements for microsensor devices has always posed fabrication challenges since it involves multi-step synthesis processes. Herein, we demonstrate a coaxial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Evaluation of NO 2 sensing properties of these sensor devices was performed using an in-house gas sensor test station existing in our laboratory. 40 Operating temperature of the HNFs has a vital role in enhancement in sensitivity and reliability of the sensor. The sensor response ( S = [ R g − R a ]/ R a ) was monitored while purging of 1 ppm NO 2 gas with varying temperatures between 50 and 350 °C for pristine ZnO, n-ZnO/p-Bi 2 O 3 and n-ZnO/n-In 2 O 3 HNFs to determine the suitable operating temperature as shown in the insets of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of NO 2 sensing properties of these sensor devices was performed using an in-house gas sensor test station existing in our laboratory. 40 Operating temperature of the HNFs has a vital role in enhancement in sensitivity and reliability of the sensor. The sensor response ( S = [ R g − R a ]/ R a ) was monitored while purging of 1 ppm NO 2 gas with varying temperatures between 50 and 350 °C for pristine ZnO, n-ZnO/p-Bi 2 O 3 and n-ZnO/n-In 2 O 3 HNFs to determine the suitable operating temperature as shown in the insets of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of NO 2 sensing properties of these sensor devices was performed using an in-house gas sensor test station existing in our laboratory. 40…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Other researchers have treated random nanofibers by cold pressing, [ 62 ] hydrothermal method, [ 109 ] and gas‐phase polymerization [ 110 ] to develop the specific capabilities of TENGs. Hence, other advanced post‐treatments (e.g., gas–solid reaction, [ 111 ] in situ photoreduction, [ 112 ] sol–gel method [ 113 ] ) are expected to be employed for electrospun nanofibers for triboelectric materials in the near future.…”
Section: Design Of Advanced Electrospun Triboelectric Materialsmentioning
confidence: 99%
“…To overcome this limitation, several methods regarding improved coaxial electrospinning were proposed mainly by using different collectors which can provide additional forces to control the direction of the jet 39 . A collector with two parallel electrodes connected to ground and a power, respectively, to drive charged fibers moving from one electrode to the other in order to achieve directional alignment of the core‐shell fibers has become a widely used method 40–43 . G. Nair et al 44 demonstrated a single‐step fabrication strategy based on coaxial electrospinning with two parallel electrodes which can change the drawing force by electric field as the collector aimed at collecting aligned CF@AuNPs‐PtNPs/NiNPs–PtNPs nanofibers.…”
Section: Introductionmentioning
confidence: 99%